Peningkatan Kinerja Staf Melalui Bimbingan Konseling dan Studi Komparasi - Djunaidi Djunaidi (Tarbiyatuna: Jurnal Pendidikan Ilmiah, 2019)
Digitization era is a challenge and reality that must be faced and can not be avoided. Technology demand lead to increasingly fierce competition, so every organization needs Human Resources (HR) who have competence in order to work in providing excellent and satisfying services. Likewise in the world of education, the role of individual performance is needed to advance the quality of education. Without good performance, the goal will be very difficult to achieve. Thus, the performance of individual teachers is needed in the world of education. The performance of education is determined by the performance of the teachers. To improve teacher performance can be done in many ways including guidance counseling and comparative studies. Guidance counseling is a process of assistance provided by the mentor to individuals through face-to-face meetings or reciprocal relationships between the two. The goal is that the counselee has the ability to see and find the problems, then be able to solve it independently. Also expected to produce human resources or employees who have faith and piety, have a solid understanding and self-awareness basis, devote themselves professionally on the basis of the norms of his profession. Comparative Study is a learning concept carried out in different locations and environments which is an activity commonly carried out for the purpose of improving quality, expanding business, improving systems, determining new policies, improving legislation, and others.